Responses of an African graminoid (Themeda triandra Forsk.) to frequent defoliation, nitrogen, and water: a limit of adaptation to herbivory - Coughenour, M B; McNaughton, S J; Wallace, L L (Oecologia, 1985)
Themeda triandra Forsk., a medium height perennial grass common in semi-arid Africa, was collected from Serengeti National Park in Tanzania, propagated vegetatively and grown in controlled environments simulating native conditions. The experiment demonstrated mechanisms that result in inability to withstand frequent defoliation, and thus how plant-herbivore interactions are affected by plant morpho-physiology. Clipping reduced most plant yield components. After two months leaf elongation rate was greater in clipped plants, but over the whole experiment aboveground yield was unaffected by clipping. Since clipping did not stimulate growth, residual leaf area was less in clipped plants. Tillering was not stimulated by clipping so there was no mechanism to increase leaf area below the clipping height. The resulting reduced leaf area accounted for reduced root and crown production by clipped plants.